Phase transformation in mechanically alloyed and hot-pressed Nb-4Si-8B and Nb-8Si-16B alloys - Chiaradia, Carlos Edilson [UNESP]; Alkmin, Luciano Braga; Nunes, Carlos ÂNgelo; Henriques, André Rodrigues ViníCius; Maria Cortez Pereira, Gilda [UNESP]; Ramos, Alfeu Saraiva [UNESP] (Trans Tech Publications, 2014)
The work reports on the phase transformation in mechanically alloyed and hot-pressed Nb-4Si-8B and Nb-8Si-16B (at-%) alloys. Elemental powder mixtures were processed in a planetary ball mill under argon atmosphere using 300 rpm, stainless steel balls (19 mm diameter) and vials (225 mL), and a ball-to-powder weight ratio of 10:1. After dry milling for 7h, wet milling with isopropyl alcohol for more 20 min was adopted to increase the recovering of previously coldwelded Nb-4Si-8B powders. To obtain the equilibrium structures the as-milled powders were hotpressed under vacuum at 1200oC for 1 h. The as-milled powders and hot-pressed samples were characterized by X-ray diffraction, scanning electron microscopy, and energy dispersive spectrometry. XRD results revealed the presence of metastable phases in as-milled Nb-Si-B powders. The hot pressing has produced dense Nb-Si-B samples, which were formed by the Nbss, Nb3B2and Fe2Nb phases beside of other unknown Si-rich phase.
Keywords: Contamination; High-energy ball milling; Hot pressing; Niobium alloys